Extraction Behaviour of Fe3+ From Chloride Solution by Technical Grade D2 EHPA: A Comparison with the Results Obtained by Analytical Grade - Biswas, R. K.; Ali, M. R.; Begum, N. (Biological Sciences - PJSIR, 2007)
The solvent ex tract ion of Fe3 + from ch lorid e sol uti on by tech n ical grade (t.g) d i-(2-eth y l h exy l ) phosph oric acid , D2EH PA d i ssol ved i n k erosen e has been i nvesti gated over a w id e range of aq u eous acid i ty as a functi on of ph ase con tact ti me, concentrat i ons of Fe3 + , HCI , H + and Cl- i n the aq ueous ph ase, D2EH PA concentration i n the organ i c phase an d temperature and the resu l t s h ave been compared to th at reported for anal yt i ca l grade (a.g). Eq u i l i bri u m ti me i 60 m i n , com pared to 50 mi n for a.g . Na t u res of Fe3• cu n cen t rati on dependen ces Iff t: not si m i l ar a n d th e va l u · of ex tracti on ra li a r c u su a l l y h Lm d red t i m e greater for t.g. t h un for a .g. u nd r si mi l a r cond i ti on s. Th e H I depen den ce pl ot pu ss t h rn u gh a m ax i m u m and a m i n i m u m a t 1 .6 M and 1 . 1 M 1-!CI , 1·cspec t i vel y, wh ereas, these are at 1 . 2 M an d 0.3 M H CI , respec t ivel y, for a.g . At [Cl-] = 3 M, the sh ape of 1-1·dependence pl ot for t.g. reagent di ffers w id el y from t h at for th e a . g. The extract i on i s also fou n d to be i mm en esel y dependent on [Cl-] for both th e grades of extractant, b ut t h e extent of dependen ce u n der si m i l ar condition depend s on the grade of extractant u sed. The extractant dependen ces a re lower for t.g. com pared to those for a.g. Reaction s are exothermic i n h i gh er temperatu re regi on , wh ereas, t h e extract i on i s al most i ndependent of te m peratu r e i n i ts lower region s. The apparent enth a l py change , t.H va l ue i n th e h i gh er tem perature regi on 1s decreased wi th decreas i n g 1-( con cen tration i n the aqu eou s ph ase. But the opposite trend was observed w i th a. g. The l oad i n g capacity depends on the aqueous acid i ti es an d grades of D2EH PA. It is 13.05 and • 6 83 g ofFe3+ per I 00 g D2EH PA (t.g.) at [HCI] of 0.1 3 and 3 M, respecti vel y, compared to 8.38 and 3. 1 4 g of Fe3 per 1 00 g D2 EH PA (a.g.) at [HCI] of 0.05 an d I M, respecti vel y. Mecha n i sm of extraction is compl i cated by the si m ul ta , neou s extra ction s of Fe3+ , FeCI '+ , Feel;, FeC l 3 H FeCl , etc. i n both cases. I t is observed t h at 99.4 % of i ron speci es 4 extracted by D2EH PA (t.g.) i n the organ i c phase can be str i pped by 5 M HC I i n three stages at organ ic to aqueou s ph ase r atio of u n i ty. Organi c phase a fter on e cycl e can be recycl ed after add i n g 0. 72 g dni-3 mono-(2-ethy l hexyl ) phosphoric acid , M2EH PA.